Judul penelitian dalam bahasa Indonesia - Windarsari, Wiwin Riski (Banking & Management Review, 2025)
Introduction/Main Objectives: This study analyzes how Es Teh Indonesia managed a 2022 social media crisis using Situational Crisis Communication Theory (SCCT) and Image Repair Theory (IRT), focusing on the relationship among response strategies, public sentiment, and cultural interpretation. Background Problems: In Indonesia’s collectivist society, brand crises on social media are often intensified by defensive or legalistic corporate responses that run counter to audience expectations for humility and empathy. However, limited research explores how these cultural values influence crisis outcomes in non-Western contexts. Novelty: This research integrates SCCT and IRT within an Indonesian cultural framework, emphasizing how moral tone and cultural alignment affect the effectiveness of crisis communication. It extends Western crisis theories by incorporating cultural sensitivity as a contextual factor. Research Methods: A qualitative descriptive case study was conducted through content and sentiment analysis of Es Teh Indonesia’s official statements, 500 user comments on Twitter/X and Instagram, and 15 news reports, guided by SCCT and IRT categories. Findings/Results: The company’s initial defensive response, implying legal action, intensified backlash, resulting in 70.4% negative sentiment. A later accommodative tone partially restored trust but did not fully repair it due to the absence of an apology. Conclusion: Empathetic, transparent, and culturally aligned communication is more effective than defensive strategies. Successful crisis management in collectivist contexts requires humility, responsiveness, and moral accountability.